Relations between Siberian and Kazakh Khanates in 15th-16th Centuries - Z. A. Tychinskikh (Научный диалог, 2024)
This study explores the stages of interaction in the 15th-16th centuries between two Turkic post-Golden Horde states: the Siberian Khanate and the Kazakh Khanate. The role of the Kazakh factor in the ethnic history of the Siberian Tatars is examined. Primary sources such as chronicles, charters, treaties, and other published documents are utilized for analysis. It is demonstrated that the common tribal composition of these states is linked to the maintenance of close relations between their polities and institutional mechanisms inherited from the previous Golden Horde period. However, the formation of political entities (the Kazakh and Siberian Khanates) in the mid to late 15th century initiated processes leading to the emergence of distinct ethnic communities (Kazakhs and Siberian Tatars) within these states. The traditional belief in historical literature that Kuchum was a ‘Kazakh prince’ is challenged. The author disputes the position of Kazakh colleagues regarding the significant role of the ‘Kazakh’ factor, including Sultan   Urus-Muhammad, in the later period of the Siberian Khanate. The nature of Siberian-Kazakh relations in the 16th century was influenced not only by the interests of the khanates’ rulers but also by external challenges posed by the emergence of new powerful political centers and leaders. The research's relevance stems from the limited exploration of the topic and conflicting approaches to the history of the formation of the Siberian Khanate and the ethnic community of Siberian Tatars in modern historiography.